Composite materials & manufacturing - Cook, Jerome T.; Vaccari, John A.; Society of Manufacturing Engineers ([Michigan] : Society of Manufacturing Engineers, 2002)
This program explains the relationship between matrix and reinforcement materials in the production of composite parts and examines various composite manufacuring processes including manual lay-up, automated lay-up, spray-up, filament winding, pultrusion, and resin transfer molding
Title from title screen
Executive producer, Steven R. Bollinger
DVD format
Keywords: Composite materials; Manufacturing processes